Particle swarm optimization with fractional Evolution - Pires, E. J. Solteiro (2009)
This work presents a new perspective of the particle swarm optimization algorithm where the integer velocity is replaced by one of fractional order. The algorithm is tested for several well known functions and the relationship between the fractional order velocity and the convergence of the algorithm is observed. The fractional order velocity is analyzed showing that influences directly the algorithm convergence rate. The fractional calculus demonstrates a potencial for interpreting evolution of the algorithm and to control its convergence.